2017
DOI: 10.1159/000477945
|View full text |Cite
|
Sign up to set email alerts
|

Early Change in Stroke Size Performs Best in Predicting Response to Therapy

Abstract: Background: Reliable imaging biomarkers of response to therapy in acute stroke are needed. The final infarct volume and percent of early reperfusion have been used for this purpose. Early fluctuation in stroke size is a recognized phenomenon, but its utility as a biomarker for response to therapy has not been established. This study examined the clinical relevance of early change in stroke volume and compared it with the final infarct volume and percent of early reperfusion in identifying early neurologic impr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 23 publications
0
16
0
Order By: Relevance
“…The precise mechanism or mechanisms by which thrombolysis improves survival are unknown, although there is an evidence thrombolysis decreases infarct size 30 and reduces the risk of readmissions because of pneumonia, 31 although the impact on other factors is still unclear. Nevertheless, previous studies have shown that good functional outcomes in the short term (ie, within 6 months) are associated with improved long-term survival, in part because of fewer complications and more independence.…”
Section: Discussionmentioning
confidence: 99%
“…The precise mechanism or mechanisms by which thrombolysis improves survival are unknown, although there is an evidence thrombolysis decreases infarct size 30 and reduces the risk of readmissions because of pneumonia, 31 although the impact on other factors is still unclear. Nevertheless, previous studies have shown that good functional outcomes in the short term (ie, within 6 months) are associated with improved long-term survival, in part because of fewer complications and more independence.…”
Section: Discussionmentioning
confidence: 99%
“…The pretreatment PWI scan was processed to identify a region of interest (ROI) defined as having a time‐to‐peak (TTP) gadolinium concentration of greater than 4 seconds beyond normal tissue from the unaffected hemisphere. This ROI, which represents the pretreatment perfusion lesion, was then moved into the 2‐hour PWI using transformation matrices extracted from the image coregistration process . The percentage of the ROI that no longer had a TTP greater than 4 seconds was used to define the percent reperfusion (Fig ).…”
Section: Methodsmentioning
confidence: 99%
“…This ROI, which represents the pretreatment perfusion lesion, was then moved into the 2-hour PWI using transformation matrices extracted from the image coregistration process. 11 The percentage of the ROI that no longer had a TTP greater than 4 seconds was used to define the percent reperfusion (Fig 1). This can be described with the equation:…”
Section: Image Processingmentioning
confidence: 99%
“…A relatively large ischemic burden reflected by Alberta Stroke Program Early CT Score (ASPECTS) scores of 5 or 6 is often used as a reason to not proceed with EVT within 6 h of last known well, though in some cases this score could reflect injury to areas of the brain that are less eloquent, and therefore, less likely to portend a poor outcome. Other limitations of using imaging as a strict criterion for therapy eligibility include early diffusion weighted image (DWI) reversibility [42][43][44] and CT perfusion "ghost" core [45]. Similarly, the presence of preexisting disability (e.g., inability to ambulate independently) is often used as an exclusion, yet providers should interpret preexisting disability from the perspective of the individual patient, not as an immutable construct.…”
Section: Stroke and Cerebrovascular Diseasesmentioning
confidence: 99%